Rancang Bangun Sistem Bel Mikrokontroler Berbasis Android Pada SMP Setia Budi Sungailiat - Hadi Tanjung, Rangga Febri; Alfarizi, Zacky; Rindri, Yang Agita; Fujiyanti, Linda (Jurnal Inovasi Teknologi Terapan, 2025)
In The World Of Education, The Bell Is One Of The Important Innovations Used To Inform The Turn Of Time Or Important Events. This Android-Based Microcontroller Bell System Is A Form Of Development Of The Bell Innovation. This Research Was Conducted At SMP Setia Budi Sungailiat With The Aim Of Improving The Efficiency And Effectiveness Of Using The School Bell And Developing An Application That Is Easy To Use Because Based On Direct Observation, It Shows That The Use Of Electric Bells At The School Is Less Efficient. In Some Situations, When Teachers Or Staff Are Not In The Room, The Bell Is Often Rung By Students, Which Makes Its Use Less Effective. Through A Case Study Approach And Prototype Method, This Research Developed An Application That Allows Controlling The School Bell Through An Android Application. The Application Is Equipped With Features To Set The Bell Schedule To Be Rung As Well As Set The Real Time Time Automatically. The Results Show That The System Is Able To Save The Bell Schedule And Ring It According To The Specified Time And According To The Selected Sound. The Results Of Questionnaire Testing On Respondents Obtained A Percentage Value Of 80%.